Neotypification of Lecanorchis purpurea (Orchidaceae, Vanilloideae) with the discussion on the taxonomic identities of L. trachycaula, L. malaccensis, and L. betung-kerihunensis - Suetsugu, Kenji; Hsu, Tian-Chuan; Fukunaga, Hirokazu (Phytotaxa, 2018)
This paper presents a re-evaluation of the taxonomic identities of Lecanorchis trachycaula and L. betung-kerihunensis. Consequently, L. trachycaula is reduced to a synonym of L. purpurea while L. betung-kerihunensis is treated as a synonym of L. malaccensis. Because no original material of L. purpurea is existent, we designate its neotype to stabilize its taxonomic status.